Attendance at London workplaces after symptom onset: a retrospective cohort study of staff members with confirmed COVID-19. (12th January 2021) - Jain, Vageesh; Waghorn, Maria; Thorn-Heathcock, Rachel; Lamb, Peter; Bell, Anita; Addiman, Sarah
Abstract: Background: Coronavirus disease (COVID)-secure workplace guidance, including the prompt self-isolation of those with COVID-19 symptoms, is fundamental to disease control in workplaces. Despite guidance, a large number of workplace outbreaks have been observed. This study aimed to identify the proportion of symptomatic staff members attending workplaces after symptom onset or testing, and associated factors. Methods: This study of symptomatic COVID-19 cases associated with London workplaces used London Coronavirus Response Centre (LCRC) records from routine telephone calls with cases and employers, from 17th July to 10th September. For each case, symptoms, date of onset, date of testing and the last attendance at work were extracted. Univariable logistic regression was performed to investigate whether age, gender or occupation was associated with workplace attendance after the onset of symptoms. Results: Out of 130 symptomatic COVID-19 cases, 42 (32.3%) attended the workplace after their reported date of symptom onset, including 16 (12.3%) with recorded COVID-19 symptoms. Five staff members attended after COVID-19 testing. Males were 66% less likely to attend the workplace after the onset of COVID-19 symptoms compared to females (odds ratio 0.34, P  = 0.05). Age and occupation were not predictive for workplace attendance after the onset of symptoms. Conclusion: A minority of symptomatic cases attended the workplace after the onset of COVID-19 symptoms, with a smaller proportion attending after testing. Males appeared less likely to attend the workplace after the onset of COVID-19 symptoms. This study highlights the need for ongoing COVID-19 secure workplace practices and prompt self-isolation after COVID-19 symptom onset or testing.